Influence of HER2 expression on prognosis in metastatic triple-negative breast cancer—results from an international, multicenter analysis coordinated by the AGMT Study Group - Gampenrieder, SP (2022)
Background: Triple-negative breast cancer (TNBC) is associated with poor prognosis, and new treatment options are urgently needed. About 34%-39% of primary TNBCs show a low expression of human epidermal growth factor receptor 2 (HER2-low), which is a target for new anti-HER2 drugs. However, little is known about the frequency and the prognostic value of HER2-low in metastatic TNBC. Patients and methods: We retrospectively included patients with TNBC from five European countries for this international, multicenter analysis. Triple-negativity had to be shown in a metastatic site or in the primary breast tumor diagnosed simultaneously or within 3 years before metastatic disease. HER2-low was defined as immunohistochemically (IHC) 1+ or 2+ without ERBB2 gene amplification. Survival probabilities were calculated by the Kaplan-Meier method, and multivariable hazard ratios (HRs) were estimated by Cox regression models. Results: In total, 691 patients, diagnosed between January 2006 and February 2021, were assessable. The incidence of HER2-low was 32.0% [95% confidence interval (CI) 28.5% to 35.5%], with similar proportions in metastases (n = 265; 29.8%) and primary tumors (n = 425; 33.4%; P = 0.324). The median overall survival (OS) in HER2-low and HER2-0 TNBC was 18.6 and 16.1 months, respectively (HR 1.00; 95% CI 0.83-1.19; P = 0.969). Similarly, in multivariable analysis, HER2-low had no significant impact on OS (HR 0.95; 95% CI 0.79-1.13; P = 0.545). No difference in prognosis was observed between HER2 IHC 0/1+ and IHC 2+ tumors (HR 0.89; 95% CI 0.69-1.17; P = 0.414). Conclusions: In this large international dataset of metastatic TNBC, the frequency of HER2-low was 32.0%. Neither in univariable nor in multivariable analysis HER2-low showed any influence on OS.